DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Jarilkapova Naubakhar (Лучшие интеллектуальные исследования, 2023)
Annotation: This article explores the role of small businesses and private entrepreneurship in driving economic growth. It conducts a literature analysis to understand the factors influencing their development, employs various methods to assess their impact, presents the results, discusses their implications, and offers conclusions and suggestions for policymakers.